Aplikasi Fuzzy Mamdani Untuk Menentukan Tingkat Keberhasilan Dosen - Alwendi; Andi Saputra Mandopa (SMART : Jurnal Teknologi Informasi dan Komputer, 2023)
The aim of this research is to apply Fuzzy logic with the Mamdani method in assessing the Research Performance of Graha Nusantara Padangsidimpuan University Lecturers. This research was designed using Fuzzy Logic with the Mamdani method. One of the research topics that uses the application of fuzzy logic is assessment systems in the field of research. Research by Graha Nusantara University Padangsidimpuan Lecturers in the Simlitabmas Data is still in the Guidance Category to move up to the Intermediate Category. UGN Padangsidimpuan Lecturers are challenged to be able to develop, dedicate and apply the knowledge needed in research. For this reason, an application is needed that can be used to calculate and record lecturer performance in the resulting research. The aim of this research is to apply fuzzy logic using the Mamdani method in assessing the research performance of Graha Nusantara Padangsidimpuan University lecturers.